BEST PRACTICES IN LABORATORY SAFETY AND BIOSECURITY TO PREVENT ACCIDENTS - Atif Dahfer Alahmari, Mohammed Abdullah almosalam, Amn Owaid Alshammari, Noor Asaad Aljasham, Ghadah Omar Owaidh Almuzaini, Eman Ahmed Ameen Sunyur, (Chelonian Research Foundation, 2024)
Laboratory safety and biosecurity are of utmost importance to prevent accidents and ensure the well-being of researchers, staff, and the public. This essay explores the best practices in laboratory safety and biosecurity to prevent accidents. The methodology involved a thorough review of existing literature, including academic journals, books, and reputable sources. The results highlight key strategies and protocols that can be implemented to enhance laboratory safety and biosecurity. The discussion emphasizes the importance of a proactive approach to prevent accidents and mitigate risks. In conclusion, adherence to best practices in laboratory safety and biosecurity is essential to create a safe working environment in research laboratories.